Imperialismo y Capitalismo - Talledo Polo, Estela Beatriz (2022)
This Professional Sufficiency report has the purpose of presenting the learning lesson about "Imperialism and Capitalism", in the Social Sciences area, this lesson was held at Rafael Narvez Cadenillas School, Trujillo with 4th year students of the secondary level in 2021. This lesson meets the requirements and maintains the structure proposed by the National University of Trujillo, this work shows the different competences and capacities according to the Social Sciences area, the competence that will be developed is: To build Historical Interpretations. The capacities that will be developed are the following: Critically interpret diverse sources and elaborate explanations on Historical Processes, each one with its corresponding performances, the methodological strategies in relation to the subject will be developed in 50 minutes. The items to be held in this lesson are: background, commercialism, the industrial revolution, rise of monopoly capitalism and imperialism. Finally, each activity will be evaluated with an assessment rubric.